INTEGRASI KECERDASAN BUATAN DALAM SISTEM INFORMASI MANAJEMEN UNTUK PENGAMBILAN KEPUTUSAN STRATEGIS - Adelia Khirani Lubis; Muhammad Irwan Padli Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This review explores the potential of integrating artificial intelligence (AI) in management information systems (MIS) to improve the quality of strategic decision-making. This article discusses the various ways in which AI can be integrated into a SIM, the benefits gained, and the challenges faced in its implementation. In addition, this research will also propose a comprehensive framework for integrating AI in a SIM, including technical, organizational, and ethical aspects. The research results are expected to provide insights for decision-makers in utilizing AI technology to improve organizational performance.